Inhibition of the brain cytochrome P450 aromatase isoform expression in Jenynsia multidentata reflects changes in water quality - Guyón, Noelia Fernanda (2012)
Cytochrome P450 aromatase is the steroidogenic enzyme that catalyzes the conversion of androgens to estrogens. Teleosts express two structurally and functionally different P450 aromatase isoforms, termed Cytochrome 19a1a and Cytochrome 19a1b. The first is preferentially expressed in ovary while the second is constitutively expressed in brain. The aim of the present study was to evaluate changes in cyp19a1b expression in brain of Jenynsia multidentata collected in Suquía river (Córdoba, Argentina) in order to assess if this biological response reflects changes in water quality. For this purpose we first identified cyp19a1b parcial cDNA sequence and adjusted the method to quantify mRNA expression by qRT-PCR (quantitative RT-PCR). Then, water and fish samples were collected in five monitoring stations located along a pollution gradient in Suquía river. The qRT-PCR analysis of female brains reveals that cyp19a1b mRNA levels change as water pollution does, showing the highest levels at both unpolluted and recovered areas, with suppression as pollution increases. Even when cyp19a1b expression in J. multidentata will need further studies, the results here presented indicate that this biological response appear as a promising biomarker of water pollution that may also point out the probable presence of endocrine disruptors.